Growth and adjustment in IMF-supported programs: evaluation report 2021 - International Monetary Fund. Independent Evaluation Office; Kim, Jun Il (Washington, D.C International Monetary Fund (IMF), 2021)
This evaluation assesses how well IMF-supported programs have helped to sustain economic growth while delivering adjustment needed for external viability. It focuses on IMF financing arrangements over the period 2008–19, under both the General Resources Account (GRA) and the Poverty Reduction and Growth Trust (PRGT).1 While the evaluation does not assess the experience during the COVID-19 pandemic, its lessons have become even more relevant as many countries now face strong headwinds to growth as they seek IMF support for achieving durable recoveries. (IMF page)
Executive summary -- 1. Introduction -- 2. Attention to growth in IMF policies on lending and program design -- 3. Growth and adjustment outcomes of IMF-supported programs -- 4. Assessing the growth impact of IMF-supported programs -- 5. Growth aspects of macroeconomic program design -- 6. Fiscal adjustment, fiscal reforms, and growth -- 7. Structural conditions, structural reforms, and growth -- 8. Exchange rate policy, external adjustment, and growth -- 9. Market debt operations and growth -- 10. Findings, lessons, and recommendations
On t.p. verso: “This report was prepared by an IEO team led by Jun Il Kim, and including Jung Yeon Kim, Reginald Darius, Yasemin Bal Gündüz, Joshua Wojnilower,Jean-Marc Bedhat Atsebi, Kwang Yeon Lee, Jiakun Li, and Hasan Toprak."
Includes bibliographical references (P: 90-95)
Keywords: Economic development; ECONOMIC DEVELOPMENT; ECONOMIC GROWTH; ECONOMIC STABILIZATION; IMF; EVALUATION